2019
DOI: 10.48550/arxiv.1901.01903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of QAOA with Quantum and Simulated Annealing

Michael Streif,
Martin Leib

Abstract: We present a comparison between the Quantum Approximate Optimization Algorithm (QAOA) and two widely studied competing methods, Quantum Annealing (QA) and Simulated Annealing (SA). To achieve this, we define a class of optimization problems with respect to their spectral properties which are exactly solvable with QAOA. In this class, we identify instances for which QA and SA have an exponentially small probability to find the solution. Consequently, our results define a first demarcation line between QAOA, Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…Although adiabatic approaches can prepare an arbitrary state [36,37], the same can be addressed with a variational approach, e.g. variational quantum eigensolver (VQE) or QAOA, by tuning short quantum circuits [15,20,[38][39][40][41][42][43].…”
Section: Variational State Preparationmentioning
confidence: 99%
“…Although adiabatic approaches can prepare an arbitrary state [36,37], the same can be addressed with a variational approach, e.g. variational quantum eigensolver (VQE) or QAOA, by tuning short quantum circuits [15,20,[38][39][40][41][42][43].…”
Section: Variational State Preparationmentioning
confidence: 99%
“…In Ref. [41] it is shown that QAOA is able to deterministically find the solution of specially constructed optimization problems in cases where quantum annealing fail. We emphasise that QAOA is an interference-based algorithm such that non-target states interfere destructively while the target states interfere constructively.…”
Section: Variants Of Primitivesmentioning
confidence: 99%
“…The optimization task is evidently challenging for deep circuits. Several approaches have been suggested to simplify optimization including leveraging parameter concentrations [18,23] and exploiting problem symmetries [22].…”
Section: Layerwise Qaoamentioning
confidence: 99%
“…Optimization becomes increasingly challenging by considering more parameters, which increase linearly with depth. Various techniques have been developed to aid in optimization-leveraging problem symmetries [22], and parameter concentrations [18,23], which these same authors previously studied. Several heuristic strategies have been explored to speed-up this challenging outer loop optimization step.…”
Section: Introductionmentioning
confidence: 99%